Pengaruh Disiplin Kerja, Komunikasi terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervenning - Maskarto Lucky Nara Rosmadi (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
This research is to know and analyze about Work Discipline, and communication to job satisfaction and its implication to performance of field of Higher Education and High Education Office of West Java Province. The method used in this research is qualitative analysis. Methods of data collection is done by interview and questionnaire, while data processing used SPSS software version 23.00. Based on the results of research, it is found that work discipline, communication, job satisfaction and performance of employees at good level. In general, the independent variable working on job satisfaction is 0.479 or 47.90%, and communication variables to job satisfaction of 0.293 or 29.30%, and variable earnings on performance is equal to 0.783 or 78.30%. From the results of research conducted, then all the broad variables will have a significant effect on the performance of employees of Higher Education and Higher Education Department of West Java Province.